1997
DOI: 10.1542/peds.100.2.180
|View full text |Cite
|
Sign up to set email alerts
|

Associated Malformations in Infants With Cleft Lip and Palate: A Prospective, Population-based Study

Abstract: A more extensive cleft seems to be associated with a higher risk for associated malformations. Although many associated congenital defects can be detected at a physical examination, the high prevalence of congenital heart disease (16 times that of general population) may justify a routine echocardiographic screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

31
155
6
24

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 226 publications
(216 citation statements)
references
References 5 publications
31
155
6
24
Order By: Relevance
“…Recent research would indicate that 21-37% of patients might have other anomalies including: cardiovascular (24-51%), musculoskeletal, facial dysmorphia or genitourinary system disturbance 8,9 . Children with associated anomalies are more likely to have combined CLP or cleft palate, rather than cleft lip alone 8 . They are often of lower birth weight 10 .…”
Section: Associated Anomaliesmentioning
confidence: 99%
“…Recent research would indicate that 21-37% of patients might have other anomalies including: cardiovascular (24-51%), musculoskeletal, facial dysmorphia or genitourinary system disturbance 8,9 . Children with associated anomalies are more likely to have combined CLP or cleft palate, rather than cleft lip alone 8 . They are often of lower birth weight 10 .…”
Section: Associated Anomaliesmentioning
confidence: 99%
“…The Cleft lip and/or palate (CLP) is considered to be the most common congenital anomaly present in the craniofacial region (Alkofide, 2008); it has been reported as a solitary finding, or associated with other malformations in over 250 syndromes (Horswell, 1991) that occurs particularly in the central nervous, cardiac, and musculoskeletal systems (Milerad et al, 1997;Horswell).…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have also made an attempt to observe a possible relationship between race and type of cleft. Many studies revealed a higher frequency of clefts among caucasian patients in relation to individuals of African descent 6,13,14,19 . A trend towards higher rates of clefts among populations of Asian descent in relation to all other races has also been found 14 .…”
Section: Introductionmentioning
confidence: 99%